FIRST DETECTION OF NOSEMA CERANAE IN JORDAN - Haddad, Nizar Jamal (European Scientific Journal, ESJ, 2014)
Nosema diseases is known to have two infecting Apis mellifera, Nosema apis and Nosema ceranae. Historically N. apis was known to be well established pathogen of A. mellifera. Whoever N. ceranae was frequently reported to infect the honeybees during the last decade. Both N. apis and N. ceranae are now thought to be widespread across the world. Honey bees are also found to be co-infected with both species. This is the first report of N. ceranea,in Jordan with a low infestation level (23.9%) of the inspected apiaries comparing with most references, while no N. apis was found infestation was found.